The Life Experience of the Community in Using Drilled Well Water After the Flood Disaster on Health in Sirau Village - Zulfa, Aulia; Prasetya Adhi, M. Hanif (Fakultas Ilmu Kesehatan Universitas Gresik, 2025)
Drilled well water is one of the main sources of the people of Sirau Village in meeting their daily needs after the flood disaster. From the experience of people using drilled well water after the flood disaster, what they feel is the damage to household appliances and the impact on dental health because it has high iron levels and there is fine sand carried with water. Aims to find out the life experience of the people of Sirau Village in using drilled well water after the flood disaster on health. The methodology of this study uses a qualitative descriptive approach with a phenomenological approach, namely the experience of 5 informants. The results of the study show that there are 3 themes that determine people's life experiences in using drilled well water after the flood disaster. Theme 1 is about drilled well water being the main need during floods, informants said drilled well water is the main source of daily needs during floods. Theme 2 is the lack of borewells in households, informants said that people feel bad impacts on their households, such as household tools becoming crusty, vehicles that rust and clothes become yellow spots. Theme 3 is the impact of use on dental health, the informant said that teeth become corrosive due to the presence of high lime substances and when the mouthwash feels iron. And it is not good to consume for drinking. The people of Sirau Village have lived experience in using drilled well water after the flood disaster for health. The community feels the bad impact on the household and dental health.